Affective Factors on the Empowerment of Human Resources - Pouresmaeil, Laya; Baluchi, Maryam (International Journal of Management and Sustainability, 2013)
In this research three main effective factors,” Official Training”, “Delegation of Authority” and “Job Rotation” in Fars-No Cement Company and Shiraz Electric Power Distribution Company have been investigated and with comparing of the given data priority and matching of the factors will be shown. The statistical society of this research is 130 persons that all are the official employees of Fars-No Cement Company and 364 persons in Shiraz Electric Power Distribution Company and with using the Morgan table, number of 100 of the Fars-No Cement Company and number of 190 of the Shiraz Electric Power Distribution Company have been elected as sample under the Class Method. For gathering the information, it has been used the questionnaire with the 24 questions. The Validity of the questionnaire has been surveyed based on the scientific texts and its Reliability has been determined based on the index of Cronbach’s alpha, 0.891. Then with using the software of SPSS analyze the information with taking T, Fredman, Anova and Tukey tests and with comparing between these two companies, revealed that Delegation of Authority, Official Training and finally Job Rotation are orderly effective factors on empowerment of human resource.